DFT and PM3 Computational Studies of the Reaction Mechanism of the Oxidation of L-Tyrosine by Iodine in the Gas Phase - Gideon A. Shallangwa; Adamu Uzairu; Victor O. Ajibola; Hamza Abba (Graduate Program of Syiah Kuala University, 2014)
Abstract - The oxidation of L-Tyrosine by molecular iodine was studied using semi-empirical and density functional theory methods. Molecular information such as net charges, values of frontier orbital energies, composition, proportions and bonding contribution were obtained and analyzed. Thus, possible reactive sites were proposed and the reaction mechanism was postulated. The postulated transition states, intermediates and products were also computed using the PM3 and DFT methods. Computed enthalpies of the oxidation reaction at standard conditions for the PM3 and DFT calculation were 216.97 kJ/mol and -36327404.72 kJ/mol respectively. The calculated ΔGo andΔSo, for the transition states according to the DFT model were both large and negative indicating that the processes were exergonic associative substitution reactions.